Clay mineralogy in southern Africa river muds. (December 2014) - Setti, M.; Lόpez-Galindo, A.; Padoan, M.; Garzanti, E.
Abstract: The composition, morphology and crystal order of clay minerals in silt-sized sediments carried in suspensions from 25 major rivers across tropical southern Africa have been studied by X-ray diffractometry and scanning and transmission electron microscopy. Our goal was to determine the spatial variability of clay-mineral associations in diverse geological settings, and in climatic conditions ranging from humid Angola and Zambia to hyperarid Namibia and the Kalahari. Specific attention was paid to the micromorphology and chemical composition of smectite particles. The relative abundance of smectites, illite/mica, kaolinite and chlorite enabled identification of regions characterized by different physical and chemical processes: (1) negligible chemical weathering is documented in Namibia, where river muds mostly contain illite/mica or smectite derived from Damara metasedimentary or Etendeka volcanic rocks; (2) kaolinite documenting intense weathering, reaches a maximum in the Okavango, Kwando and Upper Zambezi, sourced in subequatorial Angola and Zambia; (3) suspended-load muds in the Limpopo and middle Zambezi catchments display intermediate features, with varied assemblages and smectite compositions reflecting diverse parent lithologies. Clay mineralogy and chemical composition are confirmed as a most effective tool to unravel present and past climatic conditions on a continental scale.